2017
DOI: 10.5851/kosfa.2017.37.3.456
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Calcium Powders as Replacers for Synthetic Phosphate on the Quality Properties of Ground Pork Meat Products

Abstract: The aim of this study was to identify the optimal and superior type of natural calcium for replacing phosphate in cooked ground pork products. To achieve this, 0.5% eggshell calcium (ESC), oyster shell calcium (OSC), marine algae calcium (MAC), or milk calcium (MC) was added to ground pork meat products. The effect of this substitution was studied by comparing the substituted products with products containing 0.3% phosphate blend (control). ESC was considered an ideal phosphate replacer for minimizing the cook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 17 publications
(30 reference statements)
4
17
0
Order By: Relevance
“…However, Cho et al [2017] reported significantly lower hardness, cohesiveness, springiness and chewiness when 0.3% of phosphates are replaced with 0.5% of oyster shell calcium powder in ground pork meat products. Similar results were also reported by Bae et al [2017].…”
Section: Texture Propertiessupporting
confidence: 92%
See 2 more Smart Citations
“…However, Cho et al [2017] reported significantly lower hardness, cohesiveness, springiness and chewiness when 0.3% of phosphates are replaced with 0.5% of oyster shell calcium powder in ground pork meat products. Similar results were also reported by Bae et al [2017].…”
Section: Texture Propertiessupporting
confidence: 92%
“…Phosphate and partial fat replacement resulted in higher b* and h values in all treatments compared to CONF, while signifi cantly higher chroma values were found only in CONC relative to CONF. Bae et al [2017] found no effect of phosphate (0.3%) replacement with 0.5% oyster shell powder on b* values while Cho et al [2017] reported signifi cantly lower yellowness. Though research data indicate that partial replacement of backfat in frankfurters with different oils (stabilised , 2016b], the results of this research show no signifi cant differences within C treatments with in any of the observed colour parameters on day 0.…”
Section: Colour Propertiesmentioning
confidence: 85%
See 1 more Smart Citation
“…The application of solubilized proteins ( Vann et al , 2007 ), plum ingredients ( Hooshmand and Arjmandi, 2009 ; Jarvis et al , 2012 ; Jarvis et al , 2015 ), protein hydrolysates ( Shahidi and Synowiecki, 1997 ), functional carbohydrates ( Park et al , 2008 ), and natural calcium powders ( Bae et al , 2017 ; Choi et al , 2014 ; Lee et al , 2011 , Park, 2011 ) as phosphate substitutes in meat products has been investigated in several studies. Oyster shell calcium and egg shell calcium, which may be obtained from the by-products of eggs or shellfish, are considered new candidates for the substitution of synthetic phosphates in meat products ( Bae et al , 2017 ). Oyster shell calcium is produced by calcining of shellfish such as oyster, marsh clam, and scallops.…”
Section: Introductionmentioning
confidence: 99%
“… Lee et al (2011) and Choi et al (2014) suggested that oyster calcium powder may serve as a suitable substitute for sodium tripolyphosphate in emulsion-type pork sausages or restructured pork hams. Recently, Bae et al (2017) investigated the potential utility of egg shell calcium, oyster shell calcium, marine algae calcium, or milk calcium as natural calcium-based alternatives for phosphates in cooked pork products. They found that products with egg shell calcium was the most optimal candidate for phosphate substitution, as it minimized cooking loss and contributed to the textural properties of the products.…”
Section: Introductionmentioning
confidence: 99%